Europe's Birds : An Identification Guide - Hume, Rob; Harrop, Hugh; Swash, Andy; Still, Robert (Book collections on Project MUSE., 2021)
Covering more than 900 species, and illustrated with 4,700 photographs, Europe's Birds is the most comprehensive, authoritative and ambitious single-volume photographic guide to Europe's birds ever produced. Easy-to-use, practical and accessible, this guide provides the information necessary for birdwatchers of all abilities to name any bird they see. Detailed descriptions cover the birds in all their plumages--male, female, breeding, non-breeding, adult and immatures, as well as distinctive subspecies. The clear text covers all aspects of identification, including moult and vocalizations, and provides details on range, status and habitat. An unrivalled selection of photographs, chosen to be as informative as possible, makes this a beautiful book to enjoy, as well as an up-to-date and essential source of identification knowledge. Europe's Birds is produced by the same team that created Britain's Birds, which has been described as "without doubt the best photo guide on the market" (Andy Stoddart, Rare Bird Alert). The authors include top-class wildlife photographers, writers and editors, and an imaginative, highly skilled designer. All are experienced birdwatchers themselves, who know what is needed in an identification guide for birdwatchers living or travelling in Europe.